A compact reconfigurable bandpass/lowpass filter with independent transmission zeros based on generalized NRI metamaterial. Issue 3 (29th November 2019) - Abdalla, Mahmoud A.; Choudhary, Dilip Kumar; Chaudhary, Raghvendra Kumar
Abstract: This article introduces a new design and analysis of a compact reconfigurable bandpass/lowpass filter based on compact negative refractive index metamaterial transmission line. The filter equivalent circuit has been designed as a cascade of three cells of bisected‐Π/Π configuration. The reconfigurable function was achieved using inserted switches in ON and OFF modes within the cells. The filter works as bandpass when all switches are in ON condition and for lowpass switch‐1 is in OFF and switch‐2 in ON condition. The low pass filter has 3‐dB cutoff frequency of 3.25 GHz with a selectivity of 170 dB/GHz. The bandpass filter is cantered at 3.65 GHz and has a well‐matched pass band with insertion loss of 0.2 dB and wide stop band with two transmission zeros (TZs). The frequency positions of TZs are independently varying with series and shunt loading elements. The filter performance has been validated through circuit model, electromagnetic simulation, and experimental measurements. The electrical size of bandpass filter excluding feed line is 0.22 λ g × 0.20 λ g (12 × 11 mm 2 ) at center frequency of 3.65 GHz and for lowpass filter is 0.19 λ g × 0.18 λ g at cutoff frequency of 3.25 GHz. The filter can be applied in suitable for different wireless applications.